Sustainable Tourism: A Systematic Literature Review and Bibliometric Analysis - Loureiro, Isabel (2024)
The research aims to emphasise the significance of sustainable tourism and the topics it’s being associated with. It is also intended to analyse the shift in literature during the selected time. A bibliometric analysis was conducted on highly cited documents about the Topic “sustainable tourism” from 2017 to 2022, using the Web of Science database. The analysis involved examining the number of research papers, their respective journals, co-authorship, country of origin and keywords. The keywords “sustainable tourism”, “covid-19” and “tourism” were used more frequently in the 50 articles collected. The majority of the articles were published in 2020 and 2021, coinciding with the pandemic, which demonstrates the emerging focus on sustainability given by researchers in this period. By relying on a specific database and specifically selecting highly cited papers, the study was limited. However, preferring these papers aligns with the goal of this research. The literature review synthesises the themes and perspectives from different authors and the relevance given to sustainable tourism due to the COVID-19 pandemic. It identifies key trends and viewpoints in the field while recognising its limitations and provides visual information on the topic.